Heptafluorobutyronitrile (C4F7N), Hydrolysis, a Density Functional Theory (DFT) Investigation - Muhammad Bilal Arif; Christophe Coquelet; Frank Jacquier; Carlo Adamo; Maxime Lacuve; Rachel Calvet (Chemical Engineering Transactions)
Heptafluorobutyronitrile (C4F7N) has received much consideration as an effective substitute to sulfur hexafluoride (SF6) in the electrical industrial sector over the last decade. However, liability is the key to emerging technology, and the thermoelectric aging of the insulation gases may produce unavoidable consequences that raise concerns for the operator and human safety. Recently, numerous pieces of literature mentioned the production of crystals in the form of amide and dimer (ligand) generated from the aging of C4F7N with few water molecules. It was found that the hydrolysis of fluoronitrile chemical reactions initial with the production of amide (C4H2F7NO) and following, with the addition of C4F7N molecules, accelerates the reaction to produce dimer (C8H2F14N2O) and further is the possibility to generate various range of byproducts. Thermodynamically, C4F7NH2O + C4F7N ( C8H2F14N2O is the favourable chemical reaction with a 23 kcal/mol energy barrier that generates a dimer molecule. Furthermore, in presence of paramagnetic ion (typically Cu (II)), a Cooper based complex (as purple crystals) may appear. Gibbs free energy at elevated temperature indicates the driving force is needed to accelerate the reaction except C8H2F14N2O + H2O ( C12H2F21N3O, whose energy values throughout remain consistent. Theoretical calculations reveal the water acts as a strong catalytic that can abruptly reduce the energy barrier of the initial reaction from 59 to 10 kcal mol-1 and open the pathway to generate other byproducts.